LncRNA UCA1 inhibits esophageal squamous-cell carcinoma growth by regulating the Wnt signaling pathway. Issue 9 (18th May 2016) - Wang, Xianghu; Gao, Zhikui; Liao, Juan; Shang, Muhe; Li, Xiajun; Yin, Lihong; Pu, Yuepu; Liu, Ran
ABSTRACT: Esophageal squamous-cell carcinoma (ESCC) is one of the most common tumors worldwide. Recent studies suggested that long noncoding RNAs (lncRNAs) might play a key role in regulating cellular processes and cancer progression. One of the lncRNAs, urothelial carcinoma associated 1 (UCA1), is known to be dysregulated in several cancers, including bladder carcinoma, colorectal, melanoma, breast, gastric, and ESCC. However, contributions of UCA1 to ESCC remain largely undiscovered. In order to understand the role and mechanisms underlying UCA1 in ESCC, the association of UCA1 expression with risk of esophageal cancer development was determined in 106 esophageal cancer tissues of ESCC patients and adjacent normal tissues using real-time reverse-transcription polymerase chain reaction (PCR). The relative expression of UCA1 was significantly reduced in cancer versus adjacent normal tissues suggesting an enhanced risk of esophageal cancer. To investigate the biological functions of UCA1 in ESCC, it was of interest to examine whether overexpression of UCA1 might influence cell proliferation, apoptosis, cell cycle distribution, migration, and invasion in vitro using EC109 cells. Our results demonstrated that UCA1 decreased cell proliferation, migration, invasion, and cell cycle progression of EC109 cells. Further, mRNA microarray analysis of overexpressed UCA1 in EC109 cells revealed that abnormal expression of UCA1 also inhibited the Wnt signaling pathway. Gene levels of DKK1 were elevated while C-myc fell significantly in overexpressed UCA1 EC109 cells. Interestingly, Western blot demonstrated no significant differences in relative expression of CTNNB1 (β-catenin) but marked reduction in β-catenin (active form) levels in both total and nuclear proteins. These results suggest that UCA1 may inhibit ESCC growth by regulating the Wnt signaling pathway. In conclusion, UCA1 may be a novel biomarker involved in ESCC development that may provide a potential therapeutic target for ESCC.